Penyuluhan Interaktif Mengenai Diabetes Mellitus Tipe 1 diSMK Budi Raksa Lembang (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Type 1 Diabetes Mellitus (DM) is a chronic disease caused by an autoimmune process that damages pancreatic β cells, leading to an insulin deficiency in the body. This disease is predominantly found in children and adolescents; however, knowledge regarding Type 1 DM among adolescents remains relatively low, particularly concerning risk factors, symptoms, complications, and efforts to prevent these complications. This condition underscores the importance of providing early health education within the school environment. This Community Service (PKM) activity aimed to increase adolescents' knowledge about Type 1 Diabetes Mellitus through interactive health education at SMK Budi Raksa Lembang. The activity was conducted in May 2026, targeting 28 students from grades X and XI. The methods utilized included interactive lectures, discussions, the use of PowerPoint presentations, leaflets, ice-breaking sessions, and evaluations via Quizizz-based quizzes. The results demonstrated an increase in participants' understanding, marked by an accuracy growth rising from 38% to 76% with a completion rate of 85%. Participants also showed high enthusiasm during the discussion and Q&A sessions. In conclusion, health education through interactive counseling is effective in improving adolescents' knowledge of Type 1 Diabetes Mellitus and can serve as a promotive and preventive step in shaping healthy living behaviors from school age.